Overstrength values for light frame timber wall elements based on reliability methods. (15th April 2019) - Schick, Michael; Seim, Werner
Highlights: In the context of capacity design it is indispensable to design non-ductile parts and connections with considerable overstrength. A two-step procedure is proposed: First a sensitivity analysis is carried out using first-order reliability methods. Then overstrength values are adjusted to ensure a certain level of failure probability. Statistical data for all parts and connections of a light-frame timber wall element are presented. Abstract: To ensure ductile behavior of light frame timber wall elements in the context of capacity design it is indispensable to design non-ductile parts and connections with considerable overstrength. The determination of overstrength values based on reliability methods enables to address different target failure probabilities. A two-step procedure is proposed. First a sensitivity analysis is carried out on 972 wall configurations. Within the configuration the nail diameter, the nail spacing, the sheathing material, the thickness of the sheathing, the arrangement of the sheathing, the length of the wall elements and the vertical load is varied to assess the influence of the varied parameters. Within the sensitivity analysis the overstrength values that ensure the target failure probability P f = 0.04 within the range of P f = 0.023 to P f = 0.067 are determined using first-order reliability methods. The sensitivity analysis shows that the determination of overstrength values for different parameter configurations seems not to be necessary. For the second step the wall configurations that lead to the greatest overstrength values according to first-order reliability methods are identified. For these wall configurations the failure probability is determined using Monte-Carlo-Methods. The failure probability is determined using overstrength values within the range of γ R d = 1.0 to γ R d = 2.6 and minimum dimensions for the main load carrying parts of a timber frame wall element. The overstrength values that leads to an exact failure probability of P f = 0.067 for the wall configurations are determined. The overstrength values determined on the selected wall configurations are used to calculate the failure probability for all 972 wall configurations using Monte-Carlo-Methods. Finally, overstrength values are proposed to achieve ductile failure for all considered wall configurations for a certain level of probability.